The Contribution of L.W.C. Van Den Berg’s Thoughts in Dutch Colonial Legal Politics on The Development of Religious Courts in Indonesia - Roni Pebrianto; Asasriwarni Asasriwarni; Ikhwan Matondang (AJIS: Academic Journal of Islamic Studies, 2022)
The purpose of this paper is to explore the contributions of L.W.C. Van Den Berg in Dutch colonial legal politics on the development of religious courts through the theory of reception in complexu. The focus of this research are: what are the contributions of Van Den Berg in the development of religious justice in Indonesia? Why did the Dutch colonial government accept this idea? Was it to protect the colonized people or protect their power? This type of research is a library research by focusing on sources of information originating from legal politics books, articles, journals and literature that are relevant and in sync with the object of this research. The results show that Van Den Berg had contributed to the development of religious courts in Indonesia through the receptie in complexu theory which stated that the law that applies to Muslims is Islamic law. This theory emerged after the Dutch colonial saw the reality of the application of Islamic law to society. As an implementation of this theory, Islamic law legislation was made known as the Compendium Freije. Religious courts were given the authority to carry out their legal jurisdiction according to and based on Islamic law. With this theory, the existence of the Netherlands could be accepted by the people of the Nusantara